Digital Platform for Soil Health Monitoring and Management: Requirements Specifications - Patil, Mukund; Burry, Sukanya; Gogumalla, Pranuthi; Rozario, Gilbert; Katakamshetti, Nagendra; Shaik, Jameeruddin; Choudhari, Pushpajeet (International Food Policy Research Institute, 2024)
ICRISAT is developing a digital platform for soil health monitoring (MSOIL) by integrating digital tools for data sourcing, digital soil mapping to provide a site-specific information on soil nutrient status and management options. The platform aims to integrate soil data from diverse sources, analyze it using AI/ML algorithms, and deliver customized recommendations to enhance soil health and optimize agricultural productivity. This is evolving document specifying the requirements for developing the digital platform.